Evidence for a Decline in Northern Quebec (Nunavik) Belugas - Hammill, M.O.; Lesage, V.; Gosselin, J.-F.; Bourdages, H.; de March, B.G.E.; Kingsley, M.C.S. (ARCTIC, 2004)
Systematic aerial line-transect surveys of beluga whales, Delphinapterus leucas, were conducted in James Bay, eastern Hudson Bay, and Ungava Bay from 14 August to 3 September 2001. An estimated 7901 (SE= 1744) and 1155 (SE = 507) belugas were present at the surface in the offshore areas of James Bay and Hudson Bay, respectively. An additional 39 animals were observed in estuaries during the coastal survey, resulting in an index estimate of 1194 (SE = 507) in eastern Hudson Bay. No belugas were observed in Ungava Bay. Observations from systematic surveys conducted in 1993 and 2001 were analyzed using both line-transect and strip-transect methods to allow comparisons with the strip-transect survey conducted in 1985. A population model incorporating harvest information and fitted to aerial survey data indicates that the number of belugas in eastern Hudson Bay has declined by almost half because of high harvest levels. Subsistence harvest levels must be reduced significantly if this population is to recover. Des relevés aériens systématiques de bélugas (Delphinapterus leucas) par échantillonnage en ligne ont été effectués dans la baie James, l'est de la baie d'Hudson et la baie d'Ungava du 14 août au 3 septembre 2001. On a estimé respectivement à 7901 (erreur-type = 1744) et 1155 (erreur-type = 507) le nombre de bélugas présents en surface au large des côtes de la baie James et de la baie d'Hudson. Trente-neuf individus de plus ont été observés dans les estuaires pendant le relevé côtier, produisant ainsi un indice de 1194 (erreur-type = 507) dans l'est de la baie d'Hudson. Aucun béluga n'a été vu dans la baie d'Ungava. Les observations des relevés systématiques de 1993 et de 2001 ont été analysées selon deux méthodes d'échantillonnage, en ligne et en bande, afin de permettre une comparaison avec le relevé en bande de 1985. Un modèle d'analyse des populations, intégrant les données de prélèvements et ajusté aux résultats du relevé aérien, indique que le nombre de bélugas dans la baie d'Hudson a presque diminué de ...